COLONIZING THE NARRATIVE SPACE: UNLIVABLE LIVES, UNSEEABLE STRUGGLES AND THE NECROPOLITICAL GOVERNANCE OF DIGITAL POPULATIONS - Lewis, Kelly (AoIR Selected Papers of Internet Research, 2023)
Social media provides a critical space for people at the margins to document, publish, and share content that publicizes instances of human rights violations, conflict, and dispossession. This presentation explores how asymmetrical content moderation processes, opaque platform policies, and alternative enforcement systems that are brokered through backdoor corporate-government agreements lead to the removal of this content and re-obscure life and death struggles. It introduces the notion of _platform necropolitics_ (Lewis, 2023, forthcoming) and demonstrates its theoretical resourcefulness through an examination of platform censorship of pro-Palestinian content during the May 2021 Israeli–Palestinian conflict. Platform necropolitics manifests through the sovereign logics of platforms that violently police the boundaries of speech and space–determining who has the right to speak and who has the right to appear as a legitimate digital citizen, and who does not–and that take as their object the articulations of digital subjects and enact their ‘right to kill or let live’. This framework draws together scholarship from platform studies, political theorizing, and decolonial critique to reorientate critical theorizing of platforms as technologies of necropolitical power to rethink and imagine the implications of their discursive, material, and geospatial interventions. Exploring the tensions of digital media technologies as spaces that we live _with_, _in_, and _through_, considering platforms as _political_ and _material_ actors that determine and condition the social, political, and material (in)existence of digital subjects, I examine how platforms enact forms of necropolitical governance though corporate and machinic logics that simultaneously extend and reproduce the necropolitical power of the Israeli state.